Perilaku Pencarian Informasi Mahasiswa Ilmu Perpustakaan UINSU pada Masa Pandemi Covid-19 - Elgy Wijayanti; Syafira Elvina; Rifqa Amelia; Nurul Adilla; Franindya Purwaningtyas (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The Covid-19 pandemic has brought many changes. Change is so fast that several changes have occurred in human activities. One of them is in the aspect of the world of education. At a time when the Covid-19 pandemic was declared increasingly dangerous, lectures that should have been conducted face-to-face had to be moved remotely or online. This was also experienced by the library science class in 2019. The purpose of this study was to identify differences in student information seeking behavior in meeting information needs before and during the Covid-19 pandemic. The research method used in this study is a quantitative research method, and the research sample is students who experience changes in the learning process in online classes in 2019. Keywords: information seeking behavior, information needs